(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
A group of Indian Historians described the Revolt of 1857 as people’s revolt and regarded its leaders as national Hero’s. Further, some Indian and British Historians have termed the Revolt of 1857 as the ‘Mutiny of the Sepoys’. Opinion differs among the Historians as to the nature of the Great Revolt of 1857. The revolt of 1857 is a landmark in the history of India which brought the end of the rule of British East India Company and the beginning of the rule of British Crown in India. The Revolt was initiated by the sepoys of Meerut against the British; later on the joining of civilian in the revolt gave it a new dimension.The Great Revolt of 1857 (also Indian rebellion of 1857, the Great uprising of 1857, the Great rebellion, Indian Sepoy mutiny) is regarded as India’s First War of Independence against the British rule. It was the most remarkable single event in the history of India after the establishment of British rule. It was the result of the century-old British rule in India. In comparison to the previous uprisings of the Indians, the Great Revolt of 1857 was of a greater dimension and it assumed almost an all-India character with participation of people from different sections of the society. This Revolt was initiated by the sepoys of the company. So it has been commonly termed as `Sepoy Mutiny‘. But it was not simply a revolt of the sepoys.